Ride-through strategies of thyristor controlled phase shifting transformer under grid faults - Peng LI; Jinjiao LIN; Shi CHEN (电力工程技术)
Thyristor controlled phase shifting transformer (TCPST) is a new type of power flow control equipment. Due to its series and shunt coupling topology and special connection to the power grid, it is necessary to consider the handling strategy in case of power grid faults. Based on the structure and principle of TCPST, the influence of grid fault on TCPST is analyzed in this paper. It is clarified the distribution of fault current and characteristics of overcurrent and overexcitation within TCPST. On this basis, the control strategy of TCSPT for deal with grid fault impact is proposed, and the fault state identification criterion and control sequences for the TCPST is constructed. By identifying the faults within and outside the zone of TCPST and the recovery state of power grid faults with the electrical quantities, the out of service and auto-restart strategy for TCPST are realized. The temporarily withdraw method for TCPST is used to protect equipment safety in the event of severe power grid faults. Finally, some simulations are conducted for the proposed fault ride-through strategy of TCPST. It is shown that the reliable ride-through of TCPST during power grid faults can be achieved by using the strategy, which has a good application for feasibility and effectiveness of TCPST. It is benefit to take advantage of the potential of power flow regulation function of TCPST.